Direct interaction between RecA and a CheW-like protein is required for surface-associated motility, chemotaxis and the full virulence of Acinetobacter baumannii strain ATCC 17978 - Jordi Corral; María Pérez-Varela; Jordi Barbé; Jesús Aranda (Virulence, 2020)
Acinetobacter baumannii is a nosocomial pathogen that causes multi-drug resistant infections mainly in immunocompromised patients. Although this gram-negative species lacks flagella, it is able to move over wet surfaces through a not well characterized type of movement known as surface-associated motility. In this study we demonstrate through the inactivation of the A1S_2813 gene (coding a CheW-like protein) and recA (coding a DNA damage repair and recombination protein) that both genes are involved in the surface-associated motility and chemotaxis of A. baumannii ATCC 17978 strain. In addition, we also point out that the lack of either RecA or CheW-like proteins reduces its virulence in the Caenorhabditis elegans and the Galleria mellonella animal models. Furthermore, we show through co-immunoprecipitation assays that the CheW-like protein and RecA interact and that this interaction is abolished by the introduction of the mutation S97A in one of the domains of CheW-like protein that is structurally conserved in Salmonella enterica and necessary for the RecA-CheW interaction in this bacterial species. Finally, we show that the replacement of the wild-type CheW-like protein by that presenting the S97A mutation impairs surface-associated motility, chemotaxis and virulence of A. baumannii strain ATCC 17978.